Preferensi makanan online dan timbulan sampah plastik delivery masa pandemi Covid-19 - Asri Jumadewi; Safridha Kemala Putri; Yenni Sasmita (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: the COVID-19 pandemic has affected people's preferences, namely the tendency to shop online. This change in people's tastes is supported by advances in digital technology, as a culinary delivery service. This progress allegedly has the potential to increase the use of plastic as packaging. This increase will pose a risk of packaging waste in the environment.Objectives: this study aims to describe the level of public knowledge about online food preferences and waste generation during the Covid-19 pandemic.Methods: this study used a cross-sectional design, with a purposive sampling technique of 30 respondents with inclusion criteria being online drivers who are located around the location of Jl. Daud Beureuh, Banda Aceh, and has worked for at least 1 month. Data collection was carried out by direct observation and interviews which were carried out in May 2022. The data obtained was then analyzed descriptively and the chi square correlation test.Results: the results of the descriptive study showed that online food preferences during the Covid-19 pandemic were in the increasing category by 19 people (63.3%). While knowledge about waste generation during the Covid-19 pandemic was in the positive category as many as 16 people (53.3%). The p-value = 0.44 The results of this study indicate that there is no relationship between knowledge of online food preferences and the generation of packaging waste during the Covid-19 pandemic.Conclusion: the description of the level of online food preference knowledge is increasing, while the knowledge of waste generation during the Covid-19 pandemic is positive. However, there is no correlation between online food preferences and packaging waste generation.